2008
DOI: 10.1242/dev.011759
|View full text |Cite
|
Sign up to set email alerts
|

Regulation ofDlx5andDlx6gene expression by p63 is involved in EEC and SHFM congenital limb defects

Abstract: The congenital malformation Split Hand-Foot Malformation (SHFM, or ectrodactyly) is characterized by a medial cleft of hands and feet, and missing central fingers. Five genetically distinct forms are known in humans; the most common (type-I) is linked to deletions of DSS1 and the distalless-related homeogenes DLX5 and DLX6. As Dlx5;Dlx6 double-knockout mice show a SHFM-like phenotype, the human orthologs are believed to be the disease genes. SHFM-IV and Ectrodactyly-Ectodermal dysplasia-Cleft lip (EEC) are cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
138
2
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(143 citation statements)
references
References 72 publications
(103 reference statements)
2
138
2
1
Order By: Relevance
“…15 This suggests DSS1 could also be involved in the pathogenesis of SHFM. However, studies in mice with double knockout of Dlx5 and Dlx6 showed typical ectrodactyly, 3,12 whereas Dss1 expression was normal in these mutant mice. 12,16 This suggests downregulation of DLX5 and DLX6 is sufficient to cause SHFM whereas DSS1 expression is normal.…”
Section: Review Of Literature and Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…15 This suggests DSS1 could also be involved in the pathogenesis of SHFM. However, studies in mice with double knockout of Dlx5 and Dlx6 showed typical ectrodactyly, 3,12 whereas Dss1 expression was normal in these mutant mice. 12,16 This suggests downregulation of DLX5 and DLX6 is sufficient to cause SHFM whereas DSS1 expression is normal.…”
Section: Review Of Literature and Discussionmentioning
confidence: 94%
“…In mice, Dlx transcription factors have been shown to have a key function in the development and morphogenesis of the limb skeleton. 3,12 Expression of Dlx5 and Dlx6 has been detected in the apical ectodermal ridge of the embryonic limb buds. Double knockout of Dlx5 and Dlx6 in the mouse leads to ectrodactyly.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
See 3 more Smart Citations